ANALISIS PELAYANAN PRIMA (SERVICE EXCELLENT) PADA PT. XYZ CABANG MAKASSAR DALAM PENINGKATAN KEPUASAN PELANGGAN - Fatmasari Fatmasari (AkMen JURNAL ILMIAH, 2008)
This Research is executed as a mean to know how prima service system (service excellent) what is applied by PT. XYZ Branch the Makassar in improving cutomer satisfaction. Analyse the data used is descriptively that is give the prima service system picture of PT. XYZ in the effort make-up of cutomer satisfaction. Result of research, showing, that prima service (service excellent) what is done by PT. XYZ Branch the Makassar will very influencing is make-up of cutomer satisfaction. Especial variable causing the mentioned of caused by its is prima service in post service sell the motorbike honda which have been applied by company to all its cutomer so that induce at make-up of satisfaction of cutomer by doing cooperation with the cutomer (stakeholder) to do the post service sell to the direct consumer, goodness of service and also maintenance of regency area / town, ready also spare part and purchasing return the product of motor honda from cutomer which w ish to sell the return. This matter give the positive impact at satisfaction of cutomer and also progressively the wide-speading of areal market which can be included by company in its sale